1994
DOI: 10.1172/jci117362
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of 29 kindreds with generalized and pituitary resistance to thyroid hormone. Identification of thirteen novel mutations in the thyroid hormone receptor beta gene.

Abstract: Resistance to thyroid hormone (RTH), with elevated serum free thyroid hormones and nonsuppressed thyrotropin levels, is either relatively asymptomatic, suggesting a generalized disorder (GRTH) Invest. 1994. 94:506-515.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
108
0
9

Year Published

1996
1996
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(129 citation statements)
references
References 60 publications
8
108
0
9
Order By: Relevance
“…Codon 429 of TR-␤, located adjacent to the 3Ј end of the 9th heptad of the TR dimerization region, is conserved among related members of the nuclear hormone receptor superfamily. A point mutation in codon 429, converting an arginine to a glutamine (CGG to CAG) in 1 allele, has been described by our group as well as others as a naturally occurring mutation among patients with clinically apparent CRTH (31)(32)(33)(34). We have previously demonstrated that the R429Q mutation does not impair the ability to bind ligand (32).…”
Section: Resultsmentioning
confidence: 97%
“…Codon 429 of TR-␤, located adjacent to the 3Ј end of the 9th heptad of the TR dimerization region, is conserved among related members of the nuclear hormone receptor superfamily. A point mutation in codon 429, converting an arginine to a glutamine (CGG to CAG) in 1 allele, has been described by our group as well as others as a naturally occurring mutation among patients with clinically apparent CRTH (31)(32)(33)(34). We have previously demonstrated that the R429Q mutation does not impair the ability to bind ligand (32).…”
Section: Resultsmentioning
confidence: 97%
“…3). The mutant (mut) TRβ molecules have either reduced affinity for T 3 [39,41], or abnormal interaction with one of the cofactors involved in TH action [40,42].…”
Section: Geneticsmentioning
confidence: 99%
“…This may be explained by individual differences in the distribution of TRa and TRb in the tissues (2,3,26). Moreover, variations in expression of the mutant TRb and the extent to which it inhibits the wild-type TRb (4,27) or other nuclear receptors (28) may contribute to this diversity.…”
Section: Discussionmentioning
confidence: 99%